Evaluating wind energy potential in Gorgan–Iran using two methods of Weibull distribution function - Hashemi-Tilehnoee, Mehdi; Babayani, Dayan; Khaleghi, Masoud (Center of Biomass & Renewable Energy, Diponegoro University, 2016)
In this study, wind energy characteristics of the, a city in northeast of Iran, measured at 10m height in 2014. The Gorgan airport one hour recorded data extrapolated to 50m height. The data have been statistically analyzed hourly, daily, monthly, seasonally and annually to determine the wind power potential. Weibull distribution function has been used to determine the wind power density and then the potential energy. Standard deviation method and power density method are the methods used to calculate the scaling and shaping parameters of the Weibull distribution function. The annual mean wind power calculated by the standard deviation method and the power density method is 38.98w/m2 and 41.32w/m2, respectively. By comparing the results concluded that the power density method is a better method than the standard deviation method. In addition, Gorgan wind energy potentiality categorized into class 1. So is unsuitable to utilize large wind energy turbine. Article History: Received November 21, 2015; Received in revised form January 15, 2016; Accepted February 10, 2016; Available onlineHow to Cite This Article: Babayani, D., Khaleghi, M., Tashakor, S., and Hashemi-Tilehnoee.,M. (2016) Evaluating wind energy potential in Gorgan–Iran using two methods of Weibull distribution function. Int. Journal of Renewable Energy Development, 5(1), 43-48.http://dx.doi.org/10.14710/ijred.5.1.43-48